Modeling Influence of Raltegravir Intensification on Viral Dynamics: Stability and Hopf Bifurcation (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we propose an ordinary differential equation model with logistic target cell growth to describe influence of raltegravir intensification on viral dynamics. The basic reproduction number $R_0$ is established. The infection-free equilibrium $E_0$ is globally attractive if $R_0 < 1$, while virus is uniformly persistent if $R_0 > 1$. In addition, we find that Hopf bifurcation can occur at around the positive equilibrium within certain parameter ranges. Numerical simulations are performed to illustrate theoretical results.
Keywords: Multi-stage models; Logistic target cell growth; Stability; Hopf bifurcation.